Sobre la determinación del umbral del rango del factor de intensidad de tensiones y los factores que lo afectan - Medina Bernal, Kebin Alberto; Vanegas Useche, Libardo Vicente (Ingeniería, 2022)
Context: The stress intensity factor range threshold (ΔKth) is a value below which fatigue crack propagation is insignificant. This factor is usually employed to establish the fatigue life of an engineering element. However, its determination, the way in which the different factors influence its value, and its application are still subjects of discussion. Method: This paper discusses the methods and criteria for determining ΔKth and the factors that affect it. Results: Standard ASTM experimental methods are the most used tests. However, they may prove to be inaccurate, since compression pre-cracking tests can yield conservative results. In recent years, many sound analytical and numerical methods for the determination of the threshold have been proposed. Many factors and variables can affect the value of ΔKth, such as crack closure, geometry, crack size, load characteristics, microstructure, material properties, environment, residual stresses, and mixed-mode loads. Conclusions: The threshold can be determined via standard ASTM tests or theoretical or numerical methods. Much progress has been made in this field, but more research is required to improve experimental methods and obtain analytical or numerical methods that more comprehensively capture the different complexities, factors, and variables that affect the threshold.